The Influence of Globalisation in the Formation of Legislative Theory in Indonesia - Utami, Tanti Kirana; Nurul Hidayatulah, Moh Aldi; Damar Nagara, Muhammad Abhiansyah; Saputra, Arya Riansyah (Indonesian Journal Publisher, 2025)
This study aims to analyse the extent to which globalisation has influenced the formation of legislative theory in Indonesia, as well as to examine Indonesia's efforts to maintain a balance between openness to international legal norms and the preservation of national legal characteristics. Globalisation has brought about significant changes in Indonesia's legal system, ranging from the increased adoption of international legal principles to transparency in the legislative process. This study uses a descriptive-analytical method with a normative legal approach and is supported by an empirical legal approach. Data was obtained through a literature review covering legislation, legal literature, and empirical facts related to legislative practices in a global context. The results of the study show that globalisation has encouraged a shift in legislative theory from a normative and centralised approach to a more participatory, adaptive, and democratic approach. Global influences are also reflected in the transformation of legal values that are more open to the principles of social justice, public participation, and the protection of human rights. On the other hand, Indonesia continues to show its commitment to maintaining its legal identity by incorporating the values of Pancasila, customs, and local wisdom into the legislative process. Therefore, legislative theory in Indonesia has developed as a result of dialogue between local values and global demands. This finding underscores the importance of harmonising national law in a way that not only follows global trends but also strengthens the sovereignty and identity of the nation's legal system.